Pathophysiological aspects of renal stone formation and stone types - Rabie KACHKOUL; Ghita BENJELLOUN TOUIMI; Ghita EL MOUHRI; Radouane EL HABBANI; Anissa LAHRICHI (Notulae Scientia Biologicae, 2023)
Urinary stone formation is one of the oldest and most widespread diseases known to man. The disease has a multifactorial etiology that includes anatomic, environmental, genetic, infectious, metabolic, nutritional, and most importantly socio-economic factors. It is caused by a biochemical imbalance in urine between stone-forming inhibitors and promotors in a process known as lithogenesis. The mechanisms underlying the formation and development of urinary stones are not fully understood, but it can be said that they generally begin by increased urinary supersaturation of lithiasis promoters in the urine, followed by nucleation and aggregation. Subsequently, the crystals combine with other crystals in solution to form agglomerates that accumulate in the kidney. Free radical-mediated oxalate-induced renal membrane damage promotes crystal retention at the surface of the renal papilla, as well as crystal nucleation at lower supersaturation levels. In addition, stone type identification is of great interest in guiding the physician to an effective diagnosis, which allows to determine the causes in order to treat the disease and prevent recurrence. In this context, this present study reviews current knowledge on the pathophysiological aspects of kidney stone formation as well as the type of stones.